Analyzing The Use Of Kb Pill Contraception Equipment With Hypertension In Fertilizer Age Women - Araviq A.Hanyala (Journal of Applied Nursing and Health, 2020)
Hypertension in couples of childbearing age can be caused by the use of hormonal birth control which continues to be used by women of childbearing age, it can cause fatal complications, such as heart attacks, strokes and kidney failure. Hypertension can also cause blindness, irregular heart rhythms and heart failure. The aim of analyzing the effect of contraceptive use is the birth control pill with the incidence of hypertension in women of childbearing age in the village of Paleleh, Paleleh District, Buol District. The design used in the study was a cross sectional survey. Population is all women of childbearing age who have become KB pill acceptors. The sample size was 40 respondents using Accidental sampling technique. The independent variable of the study was the use of pill contraception. The dependent variable is the incidence of hypertension. Data was collected using a questionnaire, then data were analyzed using the Spearman Rho test, with a significance level of α ≤ 0.05. The results of the study showed that at most respondents had a duration of using the Pill for 24 months as many as 10 respondents (52.6%), the incidence of stage 2 hypertension was 15 respondents (37.5%), the results showed that the statistical test obtained p = 0,000 with a = 0.05, which means that H0 is rejected and H1 is accepted so that it can be interpreted that there is a significant relationship on the variable length of birth control pills with the incidence of hypertension, with a correlation coefficient of 0.851 which means having a strong relationship. Birth control pills can affect blood pressure which can cause hypertension in women of childbearing age.